NÃO TEMAS! GRITEI POR TEU NOME: Estudo da concepção materna de Javé em Dêutero- Isaías a partir da análise exegética de Is 43,1-7 - Matos, Sue Hellen Monteiro de (2013)
This exegetical study aims to demonstrate the maternal face of Yahweh revealed in the writings of Deutero-Isaiah, having as main source the oracle of salvation Is 43.1-7. To this end, we start from the analysis of the literary context, historical and religious Deutero-Isaiah, so that make the exegetical analysis of the text proposed by which we will focus, among various contents, the characteristic maternal presented in the passage. Understanding a text arises within a social environment, will highlight, based on the writings Deutero-Isaiah, the exiled community to which they are addressed prophets and prophetesses. Finally, combining the attributes of maternal goddesses Asherah and Ishtar with the fledgling maternal conception of Yahweh made by Hosea, we propose the maternal face of God based on texts of Deutero-Isaiah, in particular Is 43.1 to 7.